Nigella sativa l. as a potential phytotherapy for covid-19: A mini-review of in-silico studies (2020)
Background Coronaviruses are responsible for several human diseases such as the pandemic infectious disease 2019 (COVID-19) which is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Nigella sativa (NS) is a natural food supplement with a known safety profile that may provide a wealth of known antiviral compounds. Objective To explore the studies supporting the NS potential for hitting SARS-CoV-2 targets. Methods A literature search for scientific published or preprint in-silico studies between 1990 and 2020 in electronic databases (PubMed, Science Direct, Scopus, and Google Scholar) was performed for the terms Nigella sativa, black seed, coronavirus, SARS-CoV-2 and COVID-19. Results At least eight in-silico studies have shown that some compounds of NS, including Nigelledine, α-Hederin, Hederagenin, Thymohydroquinone, and Thymoquinone, had high to moderate affinity with SARS-CoV-2 enzymes and proteins. These compounds may potentially inhibit SARS-CoV-2 replication and attachment to host cell receptors. Conclusions These preliminary data propose NS as a potential phytotherapy candidate for COVID-19. Further preclinical experimental evidence is required followed by a phase 1 clinical trial. Keywords: SARS-CoV-2; COVID-19; Coronavirus; In-silico; Nigella sativa Running Title: Nigella sativa in COVID-19